PARTISIPASI MASYARAKAT DALAM UPAYA PEMANFAATAN LIMBAH TAHU DI KECAMATAN BANDUNGAN, KABUPATEN SEMARANG - Arif Sofianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
Bandungan subdistrict, Semarang regency is one of the main industrial centers of tofu industry. Liquid waste out of tofu industry potentially to be processed into biogas, on the other hand if it is not managed will be the environmental contamination. Government of Semarang District has been providing assistance 2 units of biogas processing equipment to "Damai" group members. Assistance provided in the form of a biogas processing plant complete unit consisting of tank, digesters, sewage tank and filters as well as devices equipped with gas stove. Currently processing biogas utilization has not been optimal, there are still a lot of waste is wasted. The aim of research to determine the potential treatment and constraints of tofu wastewater into biogas. This research method is descriptive qualitative. Informants in this study were local government officials, the owner of tofu industry and workers in Bandungan subdistrict, Semarang regency. Data collected through interviews, questionnaires, Focused Group Discussion (FGD), and observation. Analysis of the data in this study using an interactive approach developed by Miles and Huberman. The study was conducted in June-September 2016. The conclusion of this study is that the utilization of liquid tofu wastewater into biogas in Bandungan has the potential to be developed with several notes, namely: the need for technological improvements, addition of supporting materials (cow feces), user behavior changing and the participation of communities. There is a need to experiment with the model of adding cow feces that enrich the number of waste decomposing microorganisms, planting disciplinary behavior of the perpetrators, especially in the operation, ingestion of materials and care as well as comprehensive dissemination both to users and surrounding communities.